The Study of Mathematics Learning Achievement on Fraction by Using Cooperative Learning TGT Technique Combined with the Mathematics Board Games for Grade 7 Students - Sangsri, Krongphet; Chuangsoongnern, Rattanaporn; Srisiriwat, Tanawat (An Online Journal of Education, 2026)
The objectives of this quasi experimental research were to: 1) compare the mathematics learning achievement on the topic of fractions of grade 7 students after using cooperative learning TGT technique combined with mathematics board games against with the 70 percent criterion, 2) evaluate the students’ satisfaction with mathematics learning on fractions by using cooperative learning TGT technique combined with mathematics board games. The sample consisted of 40 Grade 7 students from The secondary educational service area office bangkok, obtained purposive sampling. The research instruments included: 1) four lesson plans consisting on fractions, 2) a mathematics achievement test on fractions, the reliability of all the item was 0.73, 3) a set of mathematics board games on fractions, and 4) a student satisfaction questionnaire with a reliability of 0.74. Data were analyzed using percentages, arithmetic means, standard deviations, and one-sample t-test. The research revealed that: 1) the grade 7 students’ mathematics achievement on fractions after using cooperative learning TGT technique combined with mathematics board games was significantly higher than the 70 percent criterion at the .05 level, and 2) the overall grade 7 students’ satisfaction with mathematics learning on fractions by using cooperative learning TGT technique combined with mathematics board games was at the highest level (M = 4.81, SD = 0.39). These findings reflect that this instructional model is an effective approach, demonstrating consistency between academic learning outcomes and student attitudes. This suggests that the model is highly suitable for further application in mathematics education.